Use of stable and radioactive traces for airmass characterisation and application to monsoon studies - MISHRA , U.C.; RANGARAJAN, C. (MAUSAM, 2022)
Several tracers, natural and man made, can be usefully employed for studying the source region and other characteristics of airmasses constituting the monsoon circulation. These include natural radioactive materials like radon, thoron and their daughter products, man-made radioisotopes like short-lived and long-lived fission products from nuclear explosions, trace elements present in the airmasses, synthetic compounds and devices like high pressure balloons, etc. These tracers have the advantage that integrated effects can be studied over long periods and distances and regions of airmass mixing can be clearly identified. Use has been made of some of these tracers (radon daughters) during Monex-1973 expedition over the Arabian Sea and extensive measurements have also been carried out on fission product levels at a number of countrywide stations for studying monsoon circulation. The results of these studies based on the measurements made at this laboratory and elsewhere have been given to illustrate the role of such tracers. The paper also describes some of the experiments proposed to be carried out during the forthcoming Monex projects, which are expected to give useful information about the monsoon.